Mengoptimalkan Standar Mutu di Pharma 4.0 dengan Menerapkan Perilaku Mutu untuk Keunggulan di Era Digital: Tinjauan Pustaka - Thomas, Steffen; Ananta, Rusli (Cermin Dunia Kedokteran, 2025)
The pharmaceutical industry is undergoing a significant transformation with the emergence of the Pharma 4.0 concept, driven by technological advancements such as the internet of things (IoT), artificial intelligence (AI), and robotic production systems (continuous manufacturing). One crucial aspect of this transformation is the need for strong data integrity (DI) to ensure the data reliability and security related to pharmaceutical product quality. In the era of Pharma 4.0, performance data from the pharmaceutical industry can be integrated to support real-time decision-making, the presence of DI is crucial to protect consumers and comply with industry regulations. The ALCOA+ principle is used to ensure the integrity of data throughout its lifecycle, including identification, sustainability, and availability of data. Quality behavior is needed to enhance self-awareness in the 4.0 transformation, especially with the increasing focus on cybersecurity and the rising number of data integrity cases, particularly in implementing the ALCOA+ principle. Quality behavior becomes crucial in addressing the challenges and opportunities presented by the Pharma 4.0 transformation and in maintaining data integrity in pharmaceutical industry.